2006
DOI: 10.1007/s11596-006-0427-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of morphine, fentanyl and tramadol on human immune response

Abstract: Morphine has been reported to suppress human immune response. We aimed to observe the effects of morphine, fentanyl and tramadol on NF-kappa B and IL-2 from both laboratory and clinical perspective. Jurkat cells were incubated with ten times clinically relevant concentrations of morphine, fentanyl and tramadol before being stimulated with PMA. NF-kappa B binding activity and IL-2 levels were measured. In the clinical study, 150 consenting patients were randomized into 3 groups according to the analgesics used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…In our study, there was an increase in the postoperative levels of IL-6, CRP (indicators of acute-phase and inflammatory mediator responses), and cortisol levels, and such increases were significantly less evident in tramadol patients. These results are in agreement with other studies which stated that tramadol could enhance secretion of IL-2 and Natural Killer cell activity [ 13 19 ]. These finding may also be related to the postoperative pain experienced by patients in each group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, there was an increase in the postoperative levels of IL-6, CRP (indicators of acute-phase and inflammatory mediator responses), and cortisol levels, and such increases were significantly less evident in tramadol patients. These results are in agreement with other studies which stated that tramadol could enhance secretion of IL-2 and Natural Killer cell activity [ 13 19 ]. These finding may also be related to the postoperative pain experienced by patients in each group.…”
Section: Discussionsupporting
confidence: 93%
“…Optimal and longer postoperative pain relief could be an explanation for lower levels of IL-6 within the tramadol group, especially that these types of inflammatory mediators are correlated to the hyperalgesic states [ 20 21 ]. Thus, increased production of pro-inflammatory cytokines may contribute to more severe pain and vice versa [ 19 ]. In a comparative study done by Senel and his colleagues, caudal bupivacaine 0.25% (1 ml/kg) with the addition of Tramadol 1.5 mg/kg has resulted in significantly longer postoperative analgesia duration of 13 ± 2.2 h, and these results agree with our finding [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The parturition results in tissue injury and triggers inflammation; thus, immune systems play important parts in parturition and post‐partum recovery . In the past two decades, opiate anaesthetics have been reported to exert different regulations on immune systems and contribute to the development of post‐injury immunosuppression . The hypothesis is that opiate anaesthetics might conduct immunoregulatory functions in tissue recovery and inflammation modulation in parturition and post‐partum terms.…”
Section: Introductionmentioning
confidence: 99%
“…Codeine has been shown to increase IL-8 and TNF-α production 8. In postoperative studies, morphine has been reported to inhibit IL-2 production, which was unaffected by fentanyl and either unaffected or increased by tramadol 44 45…”
Section: Discussionmentioning
confidence: 99%